Linguistic-Cognitive Text Model “Description” - Y. N. Varfolomeeva (Научный диалог)
The article is devoted to questions of explicitation of a “description” type text model. The theory of functional-semantic types of speech, developed in the 70s of the XX century by O. A. Nechaeva, is characterized. The relevance of the work is due to the importance of determining the place of this theory in modern linguistic science. The question is raised about the revision of certain provisions of the functional-semantic approach in the light of new linguistic research. The author of the article indicates that, in particular, one should take into account the element of the “point of view” model, that is, the position from which the description is made, since it is crucial in describing the sensory sensations that form the basis of the descriptive fragment. It is proved that, contrary to the established research tradition, it is necessary to take into account the role of the narrator when analyzing an artistic descriptive text. It seems important for characterizing the author’s individual style and his intentions. The article focuses on revising the composition of a text model of the “description” type in the light of the linguistic-cognitive approach. The presence of a description of a fixed background and cognitively distinguished figures as part of the model is stated. It is proved that, in addition to the background and figures, the observer's position should be included in the description model, which determines the description method, its tonality and the choice of language means of verbalization of space. The possibility of using frame analysis in the study of descriptive fragments is noted.